THERE IS AND WILL BE THE SHORTAGE OF DOCTORS/PHYSICIANS IN PAKISTAN: POINT TO PONDER. - Rano Mal Piryani1 , Suneel Piryani2, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
There is shortage of doctors globally and will probably continue in years to come. Here, we brief the situation of two countries United States of America (USA) and Pakistan. A report released in June 2021 by Association of American Medical Colleges (AAMC) “The Complexities of Physician Supply and Demands: Projection 2019-2034” has projected shortage between 37,800 and 124,000 by year 2034 in USA. It specifically mentions about shortage of primary-carephysicians between 17800 and 48000 and non-primary-care physicians including surgical-specialties, medical-specialties and other-specialties between 21000 and 77100. The report cites shortage of physicians impedes efforts to eliminate hurdles to provide high-quality care to populations and highlights how gaps will be filled.1